Internalization of the Character of Nationalism through Learning in Schools: Implementation and Challenges - Maulani, Maulani; Umasih, Umasih; Rochalina, Corry Iriani (Journal of Education Reseach and Evaluation, 2022)
A moral crisis has occurred in this nation. If you look at the reality in today's life, there are many cases that show that the nation's morale has declined. This study aims to analyze the challenges faced by teachers and the efforts made in the implementation of character-based history learning. The type of research conducted is a case study. The samples of this research are history teachers, students of class X and class XI. Data collection method used by observation, interview guide, framework as research instrument. Data analysis method is qualitative data analysis. The technique of collecting data is triangulation and then data analysis through three paths, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that the difficulties faced by history teachers in character education-based learning are difficulties in including the value of the proposition-based character according to the KD, dominant learning is not interactive, and students' character or behavior is difficult to monitor. On the other hand, training in learning that supports character education has been given to teachers, but the competence/skills of teachers need to be improved, and the learning designs made by teachers are still weak in supporting character education. Efforts to answer this challenge can be overcome by increasing teacher understanding/mastery of the concept of character education. So it can be concluded that teachers have challenges in integrating character education in students. The implications of this research can have an impact on students in improving their character for the better.